Hubungan Antara Support System Dengan DAS (Depression, Anxiety, Stress) Pada Perempuan Yang Menikah Di Usia Dini Di Kecamatan Sirimau, Kota Ambon - Warella, Nathalia Iblora; Desi, Desi; Lahade, John Radius (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
AbstractThe Relationship between Support System with the DAS (Depression, Anxiety and Stress) in Women Married at Early Age in Sirimau District, Ambon CityBackground Marriage at an early age is a marriage between a man and a woman who has not reached the age of 19. Teens who marry at an early age can experience an impact on their personal life, one of which is the psychological impact such as they experience depression, anxiety, stress. Psychological maturity is one of the reasons they can experience psychological impacts, for that they need a support system or social support. Destination of the study was to describe the relationship between support systems and depression, anxiety, stress in women who marry at an early age. Method used is quantitative research. Method used stratified random sampling technique in women who married at an early age in Sirimau sub-district, Ambon city and obtained 33 respondents. Data analysis used STATA 13 and Pearson Product Moment correlation test with a significance level of 0.05. Result show that there is a strong negative relationship in the support system for each variable of Depression, Anxiety and Stress. Conclusion the support system has a strong negative relationship with depression, anxiety and stress in women who marry at an early age in Sirimau district, Ambon city. That is, the better the support system that is built / provided, the lower the watershed level will be.Keywords: Anxiety, Depression, and Stress, Marriage at an Early Age, Support System.